Correlations and path analysis of technological properties and the lint yield of cotton - Hoogerheide, Eulália Soler Sobreira; Vencovsky, Roland; Farias, Francisco José Correia; Freire, Elêusio Curvêlo; Arantes, Eurípedes Maximiano (Pesquisa Agropecuaria Brasileira, 2007)
The purpose of this work was to study the relations between technological properties (independent variables) and the lint yield of cotton (dependent variable). The technological properties analyze were: micronaire, strength, length, uniformity of length, elongation and index of thread spinning. Twelve cotton cultivars were evaluated, in Mato Grosso State, during the 2000/2001 crop season. Correlations and other parameters for path analysis were estimated, according to Wright. The trait micronaire showed the highest direct effect on lint yield; in addition, strength, length and elongation were secondary effects. The uniformity of length and the spinning inder showed indirect effect on micronaire. A restricted selection is necessary to eliminate the negative indirect effect of the spinning index on micronaire.